Identifying Coverage Perimeter of Heterogeneous Wireless Sensor Networks - Osamy, Walid; Khedr, Ahmed M. (INFOCOMP Journal of Computer Science, 2009)
Perimeter surveillance is one of the major applications of sensor networks. The perimeter represents the physical extent of the region to be monitored and depending on the application, it is required to sense the intrusion enter the monitored region or leave from the monitored region of the object being monitored. In this paper, the problem of identifying the perimeter of the wireless network’s coverage region is addressed. We present a distributed algorithm to find out those sensor nodes that are on the perimeter of coverage (or coverage holes) in the region. We have considered random sensor networks that have sensor nodes with heterogeneous sensing ranges. Our proposed algorithm uses the location neighborhood information to determine if the sensor node enclosed by neighboring nodes, and consequently, if it is located within the interior of the wireless sensor network. We provide performance metrics to analyze the performance of our approach and the simulation shows that the algorithm provides fairly accurate results.